2013
DOI: 10.1007/s11657-013-0136-1
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis in the European Union: medical management, epidemiology and economic burden

Abstract: Summary This report describes the epidemiology, burden, and treatment of osteoporosis in the 27 countries of the European Union (EU27). Introduction Osteoporosis is characterized by reduced bone mass and disruption of bone architecture, resulting in increased risk of fragility fractures which represent the main clinical consequence of the disease. Fragility fractures are associated with substantial pain and suffering, disability and even death for affected patients and substantial costs to society. The aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
1,048
5
52

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,090 publications
(1,217 citation statements)
references
References 33 publications
11
1,048
5
52
Order By: Relevance
“…These include a balanced diet rich in dairy, ensuring an adequate calcium (1000 mg/day) and vitamin D (1000 IU/day) intake, regular weight-bearing exercise (40 min walk 3!/week), limiting alcohol to !3 units per day, stopping smoking, the avoidance of other bone toxins and the prevention of falls (121). In children and adolescents, physical activity is the best way to build up bone mass and strength.…”
Section: Fracture Preventionmentioning
confidence: 99%
“…These include a balanced diet rich in dairy, ensuring an adequate calcium (1000 mg/day) and vitamin D (1000 IU/day) intake, regular weight-bearing exercise (40 min walk 3!/week), limiting alcohol to !3 units per day, stopping smoking, the avoidance of other bone toxins and the prevention of falls (121). In children and adolescents, physical activity is the best way to build up bone mass and strength.…”
Section: Fracture Preventionmentioning
confidence: 99%
“…Osteoporosis (OP) is a prevalent osteodegenerative disease, with an estimated 22 million women, and 5.5 million men being affected within the EU [19]. Worldwide, it is estimated that OP results in over 8.9 million fractures annually (Table 1) [20].…”
Section: Osteoporosismentioning
confidence: 99%
“…It has been shown that a combination of these had a synergistic effect on BMD [22]. While these treatments have been suggested to slow the progression of OP, they fail to offer long-term effective solutions [19] and are associated with multiple severe side effects [23,24], and patients are typically subjected to lifelong administration.…”
Section: Osteoporosismentioning
confidence: 99%
“…A history of a fragility fracture or fractures is predictive of future fractures [3]. Fragility fractures are associated with significant pain, suffering, disability and considerable costs to society [4].…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis is defined as a generalised skeletal decrease in bone mineral density (BMD) and is an independent predictor of fragility fractures [4]. In patients with MS, reduced BMD [5], as well as an increased risk of falling [6], may increase the risk of fragility fractures, even in patients younger than 50 years old.…”
Section: Introductionmentioning
confidence: 99%